The Notes on the Cult of the Goddess Dea Dardanica in the South of Upper Moesia (A few examples from Kosovo and Metohija) - Samardžić, Gligor M. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
The paper presents the data on the cult of the goddess of Dardania (Dea Dardanica) in Kosovo and Metohija. The existence of the cult was authenticated in Kosovo and Metohija by votive arae found in the Smira village near Kosovska Vitina and in the ancient settlement Vendenis (Vindenae) near the Glavnik village in the municipality of Podujevo. A certain number of epigraph records shows the prevailing respect for the Dea Dardanica cult in this area.